Long-term outcomes for patients with peritoneal acellular mucinosis secondary to low grade appendiceal mucinous neoplasms. Issue 1 (January 2021) - Evans, T.; Aziz, O.; Chakrabarty, B.; Wilson, M.S.; Malcomson, L.; Lavelle, C.; O'Dwyer, S.T.
Abstract: Introduction: Low grade appendiceal mucinous neoplasms (LAMN) are known to metastasise to the peritoneum resulting in pseudomyxoma peritonei (PMP). Literature suggests that the long-term outcome is dependent on the cellular grade of the peritoneal histology, less is known about the risk to patients with acellular mucinosis (AM) alone. This study aims to review long-term outcomes in patients with PMP treated with Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy (CRS/HIPEC), whose peritoneal histology was AM secondary to LAMN. Methods: Pathological and treatment outcomes were collected from a prospectively maintained database between 2005 and 2019. Data was collected on patients with LAMN and AM diagnosed following CRS/HIPEC. A single institution performed the surgery and pathology reporting, samples reported by three different pathologists. Results: Of the 2079 patients with any appendiceal neoplasm referred between 2005 and 2019, 809 underwent CRS/HIPEC, 67 (8%) of those had PMP with purely AM secondary to a LAMN. In the AM group the median age was 59, 37 (55%) were female, follow up was for a median 39 (2–145) months. Inpatient mortality occurred in 1 patient (1.5%), disease specific mortality in 2 (3%), recurrence in 2 (3%) and disease progression in 1 (1.5%). Conclusion: This study has identified AM secondary to LAMN as a low risk group for recurrence following CRS/HIPEC compared with epithelial pathology. Given such a low rate of recurrence we would recommend low intensity surveillance post CRS/HIPEC. Agreed standardised pathological assessment is required to exclude cellular material in specimens and diagnose AM.